Prospects and limitations of heavy mineral analyses to discriminate preglacial/glacial transitions in Pleistocene sedimentary successions - Zieliński, Tomasz (Geologos, 2018)
The present study revolves around the identification of the stratigraphical boundary between Pleistocene formations that formed prior to the first advance of the Scandinavian ice sheet (Early Pleistocene, i.e., the so-called preglacial) and the overlying, glacially derived deposits (Middle Pleistocene). In particular, it focuses on variation in heavy mineral assemblages, which are an important tool for stratigraphers. The Neogene basement, described here, was most often the source of material that was redeposited by Early Pleistocene rivers. The geological structure and Early Pleistocene palaeogeographical scenarios for various Polish regions are discussed. Moreover, comparisons with other European preglacial formations are carried out. The mineral spectrum of Lower Pleistocene deposits is largely dependent of rocks of the Neogene and Mesozoic basement. If the incision of ancient catchments was into terrigenous rocks, the stratigraphical boundary between preglacial and glacial formations is easily determined with the help of a heavy mineral analysis. As a rule, this coincides with a noticeable change from resistant to non-resistant mineral associations. Such cases are noted for successions in central Poland and eastern England. On the other hand, outcrops of igneous or metamorphic rocks exist within preglacial river catchments in most parts of Europe. They were the local sources of non-resistant heavy minerals long before their glacial supply from the Baltic Shield. In these cases, mineralogical analysis fails in the search for the Early/Middle Pleistocene transition.